Effect of Neoadjuvant Chemoradiotherapy on Locally Advanced Rectal Mucinous Adenocarcinoma: A Propensity Score-Matched Study. (16th March 2017) - Sun, Yan-wu; Chi, Pan; Lin, Hui-ming; Lu, Xing-rong; Huang, Ying; Xu, Zong-bin; Huang, Sheng-hui; Wang, Xiao-jie
Abstract : Aims. To compare the surgical and oncological outcomes of rectal mucinous adenocarcinomas treated with neoadjuvant chemoradiotherapy versus surgery alone. Methods. A total of 167 locally advanced rectal mucinous adenocarcinoma patients treated with neoadjuvant chemoradiotherapy and surgery alone between 2008 and 2014 were matched using propensity score; the surgical and oncological outcomes were compared. Results. Ninety-six patients were matched. Postoperative morbidity was similar between groups. Sphincter preservation rate was higher in patients receiving neoadjuvant chemoradiotherapy (79.2% versus 60.4%, P = 0.045 ), especially for tumors ≥ 3 cm but ≤5 cm from the anal verge (75.0% versus 44.0%, P = 0.036 ). With a median follow-up of 54.8 months, the 5-year overall survival rate (neoadjuvant chemoradiotherapy versus surgery alone: 79.6% versus 67.1%; P = 0.599 ) and disease-free survival rate (75.6% versus 64.2%; P = 0.888 ) were similar. The 5-year local recurrence rate was lower in patients receiving neoadjuvant chemoradiotherapy (7.7% versus 26.0%, P = 0.036 ), while no difference was observed in distant metastasis. A poor response to chemoradiation was associated with higher local recurrence (P = 0.037 ). Conclusions. Compared with surgery alone, neoadjuvant chemoradiotherapy was found to increase the sphincter preservation rate and reduce local recurrence, thus being beneficial for locally advanced rectal mucinous adenocarcinoma patients.